The Quest For The Effectiveness Of Knowledge Creation - Agourram, Hafid (Journal of Knowledge Management Practice, 2009)
This paper discusses how knowledge creation in organizations can be optimized. Kolb (1985) learning styles theory is used to show that organizational knowledge is better developed when people with different learning styles interact with each others. It is argued that the misfit between Kolb (1985) learning styles would lead to better knowledge creation. The outcomes of this discussion are of high importance to knowledge based organizations as well as to groups of people who participate in dialogues and decision making.
Keywords: Knowledge creation; Knowledge management; Learning styles; Knowledge